Objective short sleep duration and 24-hour blood pressure - Abdalla, Marwah (Int J Cardiol Hypertens, 2020)
BACKGROUND: Short sleep duration is a contributor to cardiovascular disease (CVD) events and mortality. Short sleep duration is associated with an increased risk of high clinic blood pressure (BP). BP measured outside the clinic using 24-h ambulatory blood pressure monitoring (ABPM) is a better predictor of an individual's CVD risk. We examined the association between objectively-assessed sleep duration and 24-h ambulatory blood pressure (ABP). METHODS: A total of 893 working adults underwent sleep and ABPM. Participants were fitted with an ABPM device, and measures were taken at 28–30 min intervals. Objective sleep duration, and times of wakefulness and sleep during the 24-h ABPM period were derived from wrist-worn actigraphy. Linear regression, adjusted for age, sex, race/ethnicity, body mass index, smoking status, and diabetes were conducted on the relationship between sleep duration and the ABP measures. RESULTS: Mean age of participants (final n = 729, 59.5% female, 11.9% Hispanic) was 45.2 ± 10.4 y. Mean actigraphy-derived sleep duration was 6.8 ± 1.2 h. Sleep duration <6 h was associated with a 1.73 mmHg higher 24-h systolic BP (p = 0.031) and 2.17 mmHg higher 24-h diastolic BP (p < 0.001). Shorter sleep duration was not associated with mean awake or asleep systolic BP (p = 0.89 and p = 0.92) or mean awake or asleep diastolic BP (p = 0.30 and p = 0.74). CONCLUSIONS: To our knowledge, this is the largest study conducted which assessed sleep duration objectively while measuring 24-h ABP. Shorter sleep duration is associated with higher 24-h BP and potentially cardiovascular risk.